Effect of Glutamic Acid Foliar Application Concentrations on Growth and Yield Traits of Two Genotypes of Roselle (Hibiscus Sabdariffa L.) - Yaseen Obaid Noori Ahmed Sharif; Satar Abid Khaleefh; Sura Hameed Bahar AL-Janabi; Hiba jomaa Alfahdawi; Tariq Raad Thaer Al-Mafarji (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2025)
A field experiment was conducted during the summer season of 2024 in the fields of a farmer in the Koldara area, affiliated with Altun Kupri sub-district in Dibis district, located in northern Kirkuk Governorate (35o44'45.5"E, 44°07'21.5"N), approximately 23 km north of Kirkuk city. The objective was to evaluate the response of two roselle genotypes—Local Egyptian and Red Heet—to four foliar application concentrations of glutamic acid (0, 50, 100, and 150 mg L-1) on growth and yield traits. Statistical analysis showed the superiority of the Red Heet genotype in all growth and yield parameters. Foliar application of glutamic acid at 150 mg L-1 significantly enhanced most studied traits. The interaction of Red Heet with 150 mg L-1 gave the best results in terms of number of branches (32.95 branches plant-1), dry weight of sepals leaves (73.28 g), number of capsules (129.95 capsules plant-1), dry weight of capsules (256.77 g), number of seeds per capsule (25.77), and seed yield (949.11 kg ha-1).